2014
DOI: 10.1038/ncomms5084
|View full text |Cite
|
Sign up to set email alerts
|

Multi-peaked adaptive landscape for chikungunya virus evolution predicts continued fitness optimization in Aedes albopictus mosquitoes

Abstract: Host species-specific fitness landscapes largely determine the outcome of host switching during pathogen emergence. Using chikungunya virus (CHIKV) to study adaptation to a mosquito vector, we evaluated mutations associated with recently evolved sub-lineages. Multiple Aedes albopictus-adaptive fitness peaks became available after CHIKV acquired an initial adaptive (E1-A226V) substitution, permitting rapid lineage diversification observed in nature. All second-step mutations involved replacements by glutamine o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
161
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(181 citation statements)
references
References 54 publications
(83 reference statements)
5
161
0
4
Order By: Relevance
“…Further phylogenetic/reverse genetic studies of IOL CHIKV revealed a series of four independently acquired second-step, A. albopictus-adaptive mutations, all involving E2 substitutions, one of which relying also on a synergistic effect with an E3 substitution (136). Each of these mutations increases initial infection of the mosquito midgut and has little or no effect on infection of A. aegypti.…”
Section: Virusmentioning
confidence: 99%
“…Further phylogenetic/reverse genetic studies of IOL CHIKV revealed a series of four independently acquired second-step, A. albopictus-adaptive mutations, all involving E2 substitutions, one of which relying also on a synergistic effect with an E3 substitution (136). Each of these mutations increases initial infection of the mosquito midgut and has little or no effect on infection of A. aegypti.…”
Section: Virusmentioning
confidence: 99%
“…Moreover, recent study demonstrated that CHIKV strain involved in the Caribbean outbreak belongs to the Asian genotype. The Asian genotype was better transmitted by A. aegypti (although it was efficiently transmitted A. albopictus) due to the presence of a treonine in the E1-98 region which blocks the ability of Asian genotype virus to adapt to A. albopictus via E1-A226V mutation [26,30,34]. Determination of vector competence of mosquito populations is a key parameter in evaluating the risk of CHIKV transmission and spread [26].…”
Section: Vector and Reservoirmentioning
confidence: 99%
“…This seems to be linked to presence of an amino acid in the E1-98 region which blocks the ability of the Asian genotype virus to adapt to Aedes albopictus by means of the E1-A226V mutation [19][20][21]. Yet, laboratory studies showed that populations of Aedes albopictus from the Americas are able to transmit the strain from New Caledonia (NC/2011-568) belonging to the Asian genotype [20].…”
Section: Disease Background Informationmentioning
confidence: 99%